MEASURING THE EFFICIENCY OF SOCIAL ENTREPRENEURSHIP - A. N. Timokhovich; O. I. Nikuradze (Вестник университета, 2020)
The problems of measuring the efficiency of social entrepreneurship have been affected. The aim of the study is to identify the most relevant methods for measuring social value and evaluating the effects that arise as a result of the activities of social organizations. Various interpretations of the definition of the term “social entrepreneurship” have been given in the article. The main elements of the process of social entrepreneurship, features of the goal setting and risks of activities in the study area have been emphasized. The stages of planning activities in the field of social entrepreneurship have been described. The most common problems of measurements and evaluation of social effects that social entrepreneurs have to deal with in the process of carrying out activities related to the implementation of social projects: difficulty in achieving a quantitative evaluation, difficulty in predicting the long-term effect of activities, limitations on costs, time resources, indicators of accuracy and interpretation of results have been revealed. Problems in forecasting the effectiveness of social projects have been identified. The main methods that can be used by social entrepreneurs and organizations for measuring the social value and assessing impact of ongoing activities (method of cost-benefit analysis, method of social accounting, method of social return on investment, method of analysis of the main resources of efficiency) have been analysed. Recommendations for social entrepreneurs have been formulated.